Sleep in Paralympic athletes and its relationship with injuries and illnesses. (July 2022) - Silva, Andressa; Pinto Pinheiro, Larissa Santos; Silva, Samuel; Andrade, Henrique; Pereira, Andre Gustavo; Rodrigues da Silva, Flavia; Guerreiro, Renato; Barreto, Bruna; Resende, Renan; Túlio de Mello, Marco
Abstract: Objectives: To evaluate sleep characteristics and investigate the relationship of sleep with injuries and illnesses in Paralympic athletes. Design: Cross-sectional. Setting: Sports Training Center. Participants: 20 Paralympic athletes of athletics, swimming, and powerlifting. Outcomes: Injury and illnesses were recorded during the sports season through the Oslo Sports Trauma Research Center questionnaire (OSTRC-BR). Sleep-wake pattern was monitored for 2 weeks using actigraphy. Chronotype, sleep quality, sleep behavior, and sleep complaints were cross-sectionally collected. Results: Poor sleep quality and poor sleep behavior were highly prevalent. The mean total sleep time was 6.57 ± 49.91. Duration of naps ( r= −0.46; p= 0.04) was associated with occurrence of health problems; frequency of insomnia ( r= 0.51; p= 0.02), Pittsburgh Sleep Quality Index score ( r= 0.45; p= 0.04), and frequency of awakenings at night ( r= 0.58; p= 0.01) were associated with severity of health problems; frequency of movements during sleep was associated with OSTRC-BR cumulative score ( r= 0.58; p= 0.00); and frequency of nightmares was associated with OSTRC mean score. Conclusions: Paralympic athletes tend to report poor sleep quality, have poor sleep behavior and sleep less than the recommended. Insomnia symptoms, awakenings at night, movements during sleep and poor sleep quality were associated with the occurrence and/or severity of health problems. Highlights: 90% of the participants showed self-reported poor sleep quality. We found a 45% prevalence of poor sleep behavior in our sample. The participants tended to sleep below the recommended amount for adults. Poor sleep quality was associated with more severe health problems.